1997
DOI: 10.1093/ndt/12.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Muscular strength and bone mineral density in haemodialysis patients

Abstract: This study reveals the close relationship that exists between muscular strength of the proximal muscles and the BMD of proximal femur in patients undergoing haemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 2 publications
3
15
2
3
Order By: Relevance
“…Patients who receive dialysis are weak compared with healthy sedentary control subjects (19,(61)(62)(63)(64)(65), and it is likely that weakness is an important limitation to physical functioning in patients with kidney disease. We previously showed that muscle strength was an important predictor of gait speed in patients who were on dialysis (19), and Diesel et al (66) showed that isokinetic muscle strength was an important determinant of VO 2peak in a group of patients who were on dialysis.…”
Section: Resistance Exercisementioning
confidence: 99%
“…Patients who receive dialysis are weak compared with healthy sedentary control subjects (19,(61)(62)(63)(64)(65), and it is likely that weakness is an important limitation to physical functioning in patients with kidney disease. We previously showed that muscle strength was an important predictor of gait speed in patients who were on dialysis (19), and Diesel et al (66) showed that isokinetic muscle strength was an important determinant of VO 2peak in a group of patients who were on dialysis.…”
Section: Resistance Exercisementioning
confidence: 99%
“…However, when hemodialysis is started, the relationship between iPTH and low bone mass becomes complex (1,31,32). For this reason, study results are conflicting regarding the relationship between bone cycle determinators (alkaline phosphatase, calcium, phosphorous, iPTH) and BMD in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…‹leri evre böbrek yetmezli¤i olan hastalarda kemik mineral metabolizmas›ndaki bozulma sonucu osteoporozun geliflimi önemli bir sa¤l›k sorunudur. Bu çal›flmada, bu konudaki çal›flmalar›n ço¤unlu¤unda oldu¤u gibi, hastalarda osteoporozun tan›s›na yönelik olarak DXA kullan›m› tercih edilmifltir (8)(9)(10)(11)(12)(13)(14)(15) Bu çal›flmada en az alt› ayd›r hemodiyaliz uygulanmakta olan hastalar›n femur boynu T-skorlar› lomber vertebralara göre belirgin olarak düflük bulundu. Dünya Sa¤l›k Örgütünün s›n›flamas›na göre lomber bölgede hastalar›n %60'›nda osteopeni, %7'sinde osteoporoz ve femur boynunda hastalar›n %40'›nda osteopeni, %50'sinde osteoporoz belirlendi.…”
Section: G Gi Ir Ri Ifl Flunclassified
“…Literatürde bizim çal›flmam›zda oldu¤u gibi KMY de¤erleri ile yafl ve diyaliz süresi aras›ndaki iliflkiyi a盤a ç›karama-yan baflka araflt›rmalar da bulunmaktad›r (8,11,(18)(19)(20). Bunun nedeni hasta say›s›n›n az olmas›n›n yan› s›ra yafl ve diyaliz sürele-ri de¤erlerinin genifl aral›¤a da¤›lm›fl olmas› olabilir.…”
Section: G Gi Ir Ri Ifl Flunclassified
See 1 more Smart Citation